Upaya meningkatkan hasil belajar lari sprint melalui permainan hitam-hijau pada siswa kelas V SD Negeri 02 Gedanganak Ungaran Timur - Adliroh, Adliroh (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2020)
Sprint running learning of fifth grade students of Gedanganak State Elementary School 02, Ungaran Timur District, Semarang Regency Academic Year 2017/2018, many problems arise in learning with student learning outcomes that are less than the average value below the KKM 75 score specified by the teacher . To overcome this problem a play approach is used through the game black and green. Black and green game is a simple game that is useful for training the speed of reaction in running. The purpose of this study is to improve the learning outcomes of sprint running through black and green games in class V students of SD Negeri Gedanganak 02, Kecamatan Ungaran Timur, Semarang Regency in 2017/2018 Academic Year. This research uses classroom action research methods. The action in this study was divided into two cycles, in each cycle showing the development of the physical learning process on the sprint running material. The subjects of this study were 28th grade V students of Gedanganak State Elementary School 02 in the second semester of the 2017/2018 school year, totaling 28. The instruments used for data collection were observation sheets, and student performance tests. Analysis of the data used is descriptive analysis. The results showed that in the initial conditions of the pre-cycle students who achieved mastery learning in sprint running of 14.3%. Then an increase of 64.3% in the first cycle, and increased again to 89.3% in the second cycle. The results thus increase from pre cycle to end of cycle II by 75%.